2022
DOI: 10.1111/jomf.12897
|View full text |Cite
|
Sign up to set email alerts
|

Parents' work arrangements and gendered time use during the COVID‐19 pandemic

Abstract: Objective This study uses time diaries to examine how parents' work arrangements shaped their time use at home and work during the COVID‐19 pandemic. Background The pandemic transformed home and work life for parents, disrupting employment and childcare. The shift to work from home offered more flexibility to manage increased care burdens, but the lack of separation between work and family also likely contributed to more challenging work environments, especially among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The sudden changes in paid work and childcare arrangements due to the pandemic have likely introduced additional complexities to the inequality trends we identified. For instance, a recent study found that parents, particularly mothers, who could work from home due to COVID-19 significantly increased their time spent on secondary care (Lyttelton, Zang, & Musick, 2023). As remote work became more accessible for highly educated workers (Bick, Blandin, & Mertens, 2021), it is plausible that the trend of growing inequality in secondary care hours between highly educated and less educated mothers may have slowed or reversed after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The sudden changes in paid work and childcare arrangements due to the pandemic have likely introduced additional complexities to the inequality trends we identified. For instance, a recent study found that parents, particularly mothers, who could work from home due to COVID-19 significantly increased their time spent on secondary care (Lyttelton, Zang, & Musick, 2023). As remote work became more accessible for highly educated workers (Bick, Blandin, & Mertens, 2021), it is plausible that the trend of growing inequality in secondary care hours between highly educated and less educated mothers may have slowed or reversed after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the three perspectives, we would have consistent predictions relating to the heterogeneous effects of family resources. Since mothers with more resources are more likely to work from home during the pandemic and, therefore, are less likely to lose their jobs or shorten their work hours (Lyttelton, Zang, and Musick 2022), the time availability perspective would imply that gender gaps in paid work hours and domestic tasks will grow more among households with fewer resources. Subsequently, mothers with more resources are less likely to experience substantial income losses compared to their less-resourced counterparts (Bateman and Ross 2021; (online) Montenovo et al 2022).…”
Section: Hypothesesmentioning
confidence: 99%
“…and substantial impacts on nearly all aspects of work and daily life that have multifaceted implications for global gender equality (International Labour Organization 2020; Sachs et al 2020). Unprecedented widespread shifts to remote work, school closures, and job losses arising from the COVID-19 pandemic have substantially changed gender inequalities in time spent on paid and unpaid work (Alon et al 2020;Dunatchik et al 2021;Chung et al 2021;Lyttelton, Zang, and Musick 2022;Augustine and Prickett 2022). For example, in the United States, mothers faced more drastic changes than fathers in their labor market contribution, as employment in femaledominated industries tended to be more heavily affected by the pandemic than in male-dominated industries (Alon et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, women's preference to continue to work from home or hybridly can potentially embed traditional gender roles in the home as well as the workplace through the gendered use of time (Craig & Churchill, 2020; Kurowska, 2020). Recent research highlights that the pandemic entrenched traditional time usage patterns with women undertaking the bulk of domestic and caring responsibilities as families worked and studied from home (see Craig & Churchill, 2020; Craig & Churchill, 2021; Lyttelton et al., 2023; Yavorsky et al., 2021). Time use is a well‐established field of literature (see Craig, 2006; Sayer, 2005), which tends to accept concepts of time uncritically (for exceptions, see Fan & Moen, 2022; Rafnsdóttir & Heijstra, 2013) and only considers time quantitatively (Davies, 1994).…”
Section: Introductionmentioning
confidence: 99%